Augmentation of endogenous neurosteroid synthesis alters experimental status epilepticus dynamics. (14th September 2020) - Lucchi, Chiara; Costa, Anna Maria; Senn, Lara; Messina, Simone; Rustichelli, Cecilia; Biagini, Giuseppe
Abstract: Neurosteroids can modulate γ‐aminobutyric acid type A receptor‐mediated inhibitory currents. Recently, we discovered that the neurosteroids progesterone, 5α‐dihydroprogesterone, allopregnanolone, and pregnanolone are reduced in the cerebrospinal fluid of patients with status epilepticus (SE). However, it is undetermined whether neurosteroids influence SE. For this reason, first we evaluated whether the inhibitor of adrenocortical steroid production trilostane (50 mg/kg) could modify the levels of neurosteroids in the hippocampus and neocortex, and we found a remarkable increase in pregnenolone, progesterone, 5α‐dihydroprogesterone, and allopregnanolone levels using liquid chromatography tandem mass spectrometry. Second, we characterized the dynamics of SE in the presence of the varied neurosteroidal milieu by a single intraperitoneal kainic acid (KA; 15 mg/kg) injection in trilostane‐treated rats and their controls. Convulsions started in advance in the trilostane group, already appearing 90 minutes after the KA injection. In contrast to controls, convulsions prevalently developed as generalized seizures with loss of posture in the trilostane group. However, this effect was transient, and convulsions waned 2 hours before the control group. Moreover, electrocorticographic traces of convulsions were shorter in trilostane‐treated rats, especially at the 180‐minute ( P < .001) and 210‐minute ( P < .01) time points. These findings indicate that endogenous neurosteroids remarkably modulate SE dynamics.